Genome-Wide DNA Methylation Profile in Whole Blood of Patients With Chronic Spontaneous Urticaria - Qi, Yumeng; Zhang, Liming; Yang, Xiaonan; Tang, Biao; Xiao, Ting (Frontiers in Immunology, 2021)
Background Chronic spontaneous urticaria (CSU) is a common autoimmune skin disease. Little is known about the role of epigenetics in the pathogenesis of CSU. This study aimed to investigate genome-wide DNA methylation profile in whole blood of patients with CSU. Patients and Methods Genome-wide DNA methylation levels in whole blood samples of 95 Chinese Han ethnicity adult CSU patients and 95 ethnicity-, age- and sex-matched healthy controls were analyzed using Illumina 850K methylation chip. The differentially methylated genes (DMGs) were screened out and then functionally annotated by the gene ontology and the Kyoto encyclopedia of genes and genomes databases. Results A total of 439 differentially methylated positions (DMPs) (p < 0.01 and |Δβ| ≥ 0.06) were identified with 380 hypomethylated and 59 hypermethylated. The average global DNA methylation levels of the 439 DMPs in the CSU patients were significantly lower than those in the healthy controls (p < 0.001). The distribution of the 439 DMPs was wide on chromosome 1 to 22 and chromosome X. Chromosome 6 embodied the largest number of DMPs (n = 51) and their annotated genes were predominantly related to autoimmunity. The 304 annotated DMGs were mainly enriched in autoimmune disease- and immune-related pathways. A total of 41 DMPs annotated to 28 DMGs were identified when p < 0.01 and |Δβ| ≥ 0.1. Of the 28 DMGs, HLA-DPB2, HLA-DRB1, PPP2R5C, and LTF were associated with autoimmunity. CSU cases with elevated total IgE, positive anti-thyroid peroxidase IgG autoantibodies, positive anti-thyroglobulin IgG autoantibodies, angioedema, UASday > 4, or recurrent CSU showed phenotype-specific DMPs as compared with cases with normal total IgE, negative anti-thyroid peroxidase IgG autoantibodies, negative anti-thyroglobulin IgG autoantibodies, no angioedema, UASday ≤ 4, or non-recurrent CSU respectively. Conclusion This study shows a distinct genome-wide DNA methylation profile in Chinese Han ethnicity adult CSU patients and indicates a role of epigenetics in the pathogenesis of CSU. The predominant enrichment of the CSU-associated DMGs in immunological pathways provides supportive evidence for the immunopathogenesis of CSU. Future research on the CSU-associated DMPs and DMGs will help discover potential therapeutic targets for CSU.